Negotiating in India - Kumar, Rajesh (Henry Stewart Talks, 2011)
Mind set and negotiating behavior, Indian mind set, Brahmanical idealism, Anarchical individualism, Poverty syndrome, Implications of brahmanical idealism, anarchical individualism, and poverty syndrome, Learning to negotiate effectively, Managing complexity, Managing legitimacy